2005
DOI: 10.1111/j.0737-1209.2005.22111.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Effects of a Health Promotion Course for Taiwanese Nursing Students

Abstract: The purposes of this study were to (a) develop a teaching course on health promotion for nursing students in Taiwan, (b) evaluate the effects of this teaching course, and (c) understand students' appraisals of its effectiveness in helping them to change unhealthy behavior. A sample of 65 randomly selected female nursing students took an 18-week course developed by the investigators, which included 30 h of classroom lectures and 4 weeks of written reports by students chronicling the changes in their behavior. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 20 publications
4
19
0
5
Order By: Relevance
“…The difference in the scores of the experimental and control groups was significant in relation to type of diet and nutritional habits but was not significant in relation to physical activity. This result supports the results of many of the reviewed studies [21][22][23][24] and might be attributed to that it is easier to note the direct influence on behaviours that do not require much effort such as nutrition vs. behaviours related to physical activity. However, the results of a study conducted in Beijing reflected contradictory results.…”
Section: Discussionsupporting
confidence: 88%
“…The difference in the scores of the experimental and control groups was significant in relation to type of diet and nutritional habits but was not significant in relation to physical activity. This result supports the results of many of the reviewed studies [21][22][23][24] and might be attributed to that it is easier to note the direct influence on behaviours that do not require much effort such as nutrition vs. behaviours related to physical activity. However, the results of a study conducted in Beijing reflected contradictory results.…”
Section: Discussionsupporting
confidence: 88%
“…In a study carried out by Yeh et al to evaluate health promoting lifestyle behaviors of 42 nursing students who were taking public health course in Taiwan before and after taking the course, it was found that physical activity and diet behaviors of students significantly changed at the end of the course (Yeh et al, 2005). Hsiao et al evaluated the effect of health promoting training provided to nursing students, HPLP mean scores significantly increased after the training (Hsiao et al, 2005). Ayaz et al found that there was a statistically significant increase in diet and health responsibility sub-scale mean scores of the students who took health protection and promotion courses (Ayaz et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the risk of cancer was found to affect health perception negatively (20).In our study, the healthy lifestyle behaviors of the students were found to increase with increasing age and education levels. Other studies conducted with students also have found that age and education level affect healthy lifestyle behaviors positively (14,(35)(36)(37)(38)(39). The findings of our study show that students should be made aware of preventing cancer starting in their freshman year and hat high risk groups should be determined and supported.…”
Section: Does Familial History Of Cancer Affect the General Health Comentioning
confidence: 89%